Knowledge, attitude, practices (KAP), and risk factors of lumpy skin disease among livestock owners in Pakistan - Sadia, SH; Hussain, M; Saeed , MA; Aftab, T; Yousaf , A; Khan, H; Andlib, S; Riaz, S; Afzal, MS; Ali, A; Shabbir, RMK; Ahmed, H (Journal of the Hellenic Veterinary Medical Society, 2025)
Lumpy skin disease (LSD), caused by the LSDV virus, affects cattle and water buffalo, resulting in skin nodules, weight loss, and reduced milk production. In current study, a cross-sectional survey was conducted to evaluate the knowledge, attitude, practices (KAP), and risk factors associated with lumpy skin disease (LSD) in cattle among livestock owners in the Chakwal district, Punjab, Pakistan. A total of 383 livestock owners participated in the study from five different villages of district Chakwal. Data analysis was performed using SPSS, Jamovi software, while Graphpad Prism aided in creating graphical representations. The results showed that most of the participants were from Sohawa village (29%), Muslim (98.2%), male (66.8%), age group 51-60 years old (36%), Punjabi (94.3%), married (85.1%), illiterate (78.6%), and monthly income above 50,000 (42.0%). Most of the participants (77.3%) were aware of LSD while54% knew the risks involved. Regarding attitude, 67.2% of cattle owners believed that their animals were at risk while 84.1% wanted their cattle checked for illness, and 96.3% would appreciate free care if their cattle had lumpy skin disease. Concerning risk factors, 74.4% participants did not view economic instability as a significant concern, but 68.7% thought an unregulated animal husbandry system as a risk. Furthermore, 42% of respondents agreed that there is a connection between a higher disease risk and larger herd sizes while 75.2% believed that insects may spread the virus. The knowledge, attitudes, and practices of cattle owners regarding lumpy skin disease (LSD) were elucidated by the KAP study revealed that cattle owners have a LSD knowledge, risk factors awareness and positive attitude towards prevention and control, emphasizing the importance of immunization and biosecurity measures. To effectively manage LSD, educational programs, enhanced biosecurity procedures, and improved disease management strategies are recommended.